Pictet–Spengler Synthesis of Perfluoroalkylated Tetrahydro-γ-carbolines and Tetrahydropyrrolopyrazines - Voznesenskaia, Natalia G.; Shmatova, Olga I.; Nenajdenko, Valentine G. (Synthesis, 2020)
A new method for the synthesis of perfluoroalkylated derivatives of γ-carboline and pyrrolopyrazine was elaborated. Pictet–Spengler reaction of isotryptamine and 2-(pyrrol-1-yl)ethanamine with trifluoromethylated carbonyls and 2-perfluoroalkyl-substituted five-, six-, and seven-membered cyclic imines was studied. It was found that this approach opens efficient access to a family of alkaloid-like compounds bearing a CF3 or C2F5 group in the structure. In the case of the iso-Pictet–Spengler reaction with 2-perfluoroalkyl-substituted cyclic imines, a series of γ-carbolines bearing an aminoalkyl group were prepared.
Keywords: iso-Pictet–Spengler reaction; isotryptamine; fluorine; trifluoromethyl; carboline; imine